Multi-Scale Modeling of Organic Electro-Optic Materials - Johnson, Lewis E. V. D. L. (University of Washington Graduate School, 2012)
Development of organic materials for photonics applications requires simultaneous optimization of molecular and bulk properties to obtain acceptable performance in device applications. In developing organic electro-optic materials based on the Pockels effect, these properties include the molecular hyperpolarizability (β) of organic non-linear optical (ONLO) chromophores, the extent to which chromophores can be acentrically ordered in a material, the number density of chromophores (ρN), and the dielectric constant (ε) of the environment surrounding the chromophores. Furthermore, constraint of orientational degrees of freedom (reduced dimensionality) due to engineered non-covalent interactions and/or high chromophore loading can strongly affect acentric ordering of chromophores. This parameter space can be efficiently searched through theory-aided design, but the vast differences in the spatial scales needed to simulate each property require a multi-scale approach to computational modeling. Coarse-grained, rigid-body Monte Carlo (RBMC) calculations can be used to simulate large ensembles of chromophores and analyze the effects of steric anisotropy and dipole moment on ordering. Fully atomistic molecular dynamics (MD) calculations using classical force fields can be used to probe specific intermolecular interactions at the nanoscale, and electronic structure calculations at various levels (semi-empirical, DFT, and correlated, wavefunction-based methods such as MP2) can be used to calculate optical properties and provide parameters for lower-level (force field based) calculations. These techniques have been used to model the dielectric and phase behavior of strongly polar liquids such as acetonitrile, assist in the characterization of chomophore-containing complexes that exhibit a four-fold increase in poling efficiency compared to its parent chromophore, and in the molecular engineering of an OLNO dye for DNA-based biophotonics. Additionally, the importance of accounting for molecular shape, electrostatic boundary conditions, and choice of electronic structure methods are discussed and critically analyzed.